Ansiedad y su incidencia en el estado emocional de una mujer de 22 años de edad en la ciudad de Babahoyo - Sánchez Carbo, Diego Isaias (2021)
The objective of this study case is to demonstrate the influence of anxiety on the emotional state, since this action is presenting a negative impact on the psychosocial life of the patient, so that the obstacles to appreciate various stimuli and the capture of information caused by the cognitive distortions that anxiety could cause. Within the implemented methodology, a psychological technique was used such as: the Hamilton test, which measures anxiety levels in an individual. In the development of this study case , it was possible to determine that the patient has generalized anxiety caused by the automatic thoughts that the patient presents, which could also be corroborated by means of the applied techniques. In the findings, a therapeutic plan based on the demands was applied to the young woman.